Da fuga para o café à fuga para o Instagram: a exibição conspícua do tempo e a sua relação com o bem-estar subjetivo - Vasconcelos, Ernanda Gabrielly da Silva (2019)
While the researches on conspicuous consumption has traditionally analyzed how people spend money on products that symbolize status, this research seeks to investigate conspicuous consumption in relation to time and its relation as subjective well-being. Thus, the objective of this research is to understand how the conspicuous consumption of the time shown in Instagram, influences the perception of the subjective well-being from the users who demonstrate to be occupied. Based on the oral history method, the study was developed with the subjects who uses Instagram to demonstrate that they are busy with their work activity. Data were collected through observation and semi-structured interviews. The results of the research reveals that in all the relationships observed there are positive and negative perceptions about subjective well-being, since the busy lifestyle responsible for physical and psychological costs, neither the excess of work nor its exposure have made this style less aspirational life. It was observed that the conspicuous consumption of time is far beyond the individual presenting himself as busy, since displaying the free time with "conspicuous activities" provided by the work has become significant. Exploring the relationship between subjective well-being and conspicuous consumption of time can be considered the theoretical contribution of this study because it aims to improve the already consolidated literature that advocates the displacement of the traditional idea of preciousness and shortage of products for the time, and yet, has social implications in the sense of bringing a reflection on the awareness of the appropriate use of time in the subject's perspective.